Phosphatidylethanolamine: A key player in lung disease - Linlin Zhang; Wanxin Duan; Liyang Li (Clinical and Translational Discovery)
Abstract Phosphatidylethanolamine (PE) is a pivotal glycerophospholipid that constitutes a significant portion of cellular membranes, playing a crucial role in maintaining membrane fluidity, supporting protein integration, and mediating signal transduction. In the lungs, PE is also a key component of pulmonary surfactant, which is essential for preserving alveolar stability and facilitating efficient gas exchange. Recent research has highlighted the association between dysregulated PE metabolism and various lung diseases, such as asthma, pulmonary fibrosis and chronic obstructive pulmonary disease. Nevertheless, the molecular mechanisms underlying these associations remain poorly understood, and the potential of PE as a therapeutic target or biomarker for lung diseases has yet to be fully explored. This review aims to provide a comprehensive overview of the biological functions and biosynthetic pathways of PE, with a particular focus on its roles in pulmonary physiology and pathology. We summarise current findings on PE alterations in different lung diseases and discuss the potential implications of targeting PE metabolism for therapeutic interventions. Implication of PE in the aetiology of diverse diseases. The pivotal role of PE in driving lipid peroxidation during ferroptosis. Implications of PE metabolic dysregulation in pulmonary epithelial cells.